Analisis tingkat kesehatan Bank menggunakan metode Risk Based Bank Rating (RBBR) (Studi kasus pada Bank Jambi Periode Tahun 2019 – 2023) - HANIFATURASYDA, ARFINA; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2025)
The goal of this research is to evaluate Bank Jambi’s state of health during the 2019–2023 period using the Risk Based Bank Rating (RBBR) method, which includes four main aspects: risk profile, corporate governance, profitability, and capital. The data used is secondary data from Bank Jambi’s annual report, with a quantitative approach and documentation techniques. The study’s findings indicate that Bank Jambi as a whole is in the category of "Very Healthy." In terms of risk profile, an average Non-Performing Loan (NPL) of 1.5% indicates low credit risk, while an average Loan to Deposit Ratio (LDR) of 93.18% is in the category of "Quite Healthy." In terms of profitability, the average Return on Assets (ROA) of 3.23% and the average Net Interest Margin (NIM) of 5.82% reflect excellent financial performance. On the other hand, the average Capital Adequacy Ratio (CAR) of 28.37% indicates a very strong capital capacity. Despite the COVID-19 pandemic providing significant challenges, Bank Jambi has managed to maintain its financial stability. This research recommends improving liquidity management, product diversification, and digital innovation to strengthen competitiveness and operational sustainability. These findings contribute to understanding the financial health of Regional Development Banks (BPD) and their role in supporting local economic development.